2016
DOI: 10.1097/01.prs.0000479967.94459.1c
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Arnica and Mucopolysaccharide Polysulfate Attenuates Periorbital Edema and Ecchymosis in Open Rhinoplasty

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…For example, oral administrations of heparinoid are effective in the treatment of oral lichen planus . Moreover, topical heparinoid‐containing cream not only reduces postoperative ecchymosis and oedema, but also prevents the development of pressure ulcers . Furthermore, topical applications of a heparinoid‐containing product significantly increased stratum corneum hydration in both young and aged humans, as well as both epidermal growth factor receptor inhibitor‐ and radiotherapy‐induced skin dryness .…”
Section: Introductionmentioning
confidence: 99%
“…For example, oral administrations of heparinoid are effective in the treatment of oral lichen planus . Moreover, topical heparinoid‐containing cream not only reduces postoperative ecchymosis and oedema, but also prevents the development of pressure ulcers . Furthermore, topical applications of a heparinoid‐containing product significantly increased stratum corneum hydration in both young and aged humans, as well as both epidermal growth factor receptor inhibitor‐ and radiotherapy‐induced skin dryness .…”
Section: Introductionmentioning
confidence: 99%
“…Of the 11 level II evidence studies, 3 (27%) failed to elicit significant differences between treatment and control groups at their primary end points, whereas 8 (73%) showed significant benefits. Reproducible level II studies 14,16 support the use of arnica in rhinoplasty patients for reduction in early postoperative ecchymosis and edema. Similarly, reproducible level II evidence [17][18][19][20] supports the use of onion extract for improvement in scar pigmentation.…”
Section: Resultsmentioning
confidence: 88%
“…A study performed by Koşucu et al reported that keeping intraoperative mean arterial blood pressure at 50-60 mmHg reduced edema and ecchymosis (15). There are some studies about topical administration of arnica and mucopolysaccharide polysulfide cream, which reduces edema and ecchymosis (16).…”
Section: Discussionmentioning
confidence: 99%